The identification of infective filarial larvae in Simuliidae - Nelson, G. S. (1962)
Although it is recognized that the presence of animal filariae can lead to confusion in the interpretation of infection rates in mosquito vectors of filariasis, the filariae found in man-biting simuliids are usually assumed to be Onchocerca volvulus. The authors of this paper emphasize that it is unwise to calculate transmission indices from infection rates in man-biting simuliids unless there is confidence in the identification of the filarial larvae. In this respect they cite their observations on Mount Elgon in Uganda which show that the majority of the filarial larvae in Simulium neavei—the local vector of onchocerciasis—are of species that do not affect man. To assist in the correct interpretation of infection rates in the vectors the authors made a detailed study of the morphological character of O. volvulus infective larvae and established criteria for distinguishing O. volvulus from other filariae known to be transmitted by simuliids.